The Application of the Four Pillars in Improving the Education Paradigm for Soft Skills of Children Aged 5-6 Years - Rismayanti, Sri Ayu; Salwa Salsabila Amdan; Anfa Kamilatul Rosidah; Risbon Sianturi (JURNAL PENA PAUD, 2025)
This study aims to describe the implementation of United Nations Educational, Scientific and Cultural Organization (UNESCO) Four Pillars of Education in improving the soft skill education paradigm for children aged 5–6 years in PAUD institutions. The educational orientation has shifted from academic-center to a holistic, child-center approach through four main pillars: learning to know, learning to do, learning to be, and learning to live together. This qualitative research used a case study method at RA Al-Muttaqin. Data were collected through participatory observation by three researchers and in-depth interviews with two participants: the class teacher and the principal. Findings revealed that the four pillars were applied contextually in center-based learning, hands-on activities, character building, and social interaction. These practices positively contributed to the development of children's soft skills, including communication, empathy, cooperation, responsibility, and independence. The study highlights the urgency of transforming early childhood education from an academic focus to a more humanistic, integrated model. It also underlines the importance of strengthening teacher competencies and implementing a value-based curriculum to support this shift. In conclusion, the application of the Four Pillars promotes a more meaningful and effective early education experience.